2023
DOI: 10.1101/2023.06.23.23288598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 virologic rebound with nirmatrelvir-ritonavir therapy

Abstract: Objective: To compare the frequency of replication-competent virologic rebound with and without nirmatrelvir-ritonavir treatment for acute COVID-19. Secondary aims were to estimate the validity of symptoms to detect rebound and the incidence of emergent nirmatrelvir-resistance mutations after rebound. Design: Observational cohort study. Setting: Multicenter healthcare system in Boston, Massachusetts. Participants: We enrolled ambulatory adults with a positive COVID-19 test and/or a prescription for nirmatrelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We presented evidence of a statistically significant elevated risk of VBR overall from early initiation of nirmatrelvir/ritonavir as compared to later initiation (albeit with wide confidence intervals and hence high uncertainty due to the paucity of VBR events amongst late initiators). Such findings correspond to results from a small perspective cohort study, which found a statistically insignificant association between nirmatrelvir/ritonavir initiation within 0-1 days after diagnosis and VBR, and no such association for later initiation, amongst 72 ambulatory patients with a median of 4 vaccination doses 20 . The elevated VBR risk observed amongst early initiators overall may have reflected the effects of aging on nirmatrelvir/ritonavir users, many of whom are aged 60 years or above, and whom may be susceptible to immunosenescence, weakened development of T-cell response, and poorer antiviral antibody quality 21,22 , in turn hampering the rapid development of an effective immune response to sufficiently address any leftover virus subsequent to therapy cessation.…”
Section: Discussionsupporting
confidence: 86%
“…We presented evidence of a statistically significant elevated risk of VBR overall from early initiation of nirmatrelvir/ritonavir as compared to later initiation (albeit with wide confidence intervals and hence high uncertainty due to the paucity of VBR events amongst late initiators). Such findings correspond to results from a small perspective cohort study, which found a statistically insignificant association between nirmatrelvir/ritonavir initiation within 0-1 days after diagnosis and VBR, and no such association for later initiation, amongst 72 ambulatory patients with a median of 4 vaccination doses 20 . The elevated VBR risk observed amongst early initiators overall may have reflected the effects of aging on nirmatrelvir/ritonavir users, many of whom are aged 60 years or above, and whom may be susceptible to immunosenescence, weakened development of T-cell response, and poorer antiviral antibody quality 21,22 , in turn hampering the rapid development of an effective immune response to sufficiently address any leftover virus subsequent to therapy cessation.…”
Section: Discussionsupporting
confidence: 86%
“…We hypothesize that viral rebound occurs more frequently in community settings relative to the clinical trial, because infected individuals in the community are often prescribed the drug very early after symptom development, whereas in the trial, there was a natural 1 to 2-day delay based on the enrollment and consent process. Surprisingly, this short delay may have limited rebound while not affecting the primary endpoints of the trial, a finding supported by recent clinical studies 30 , which nevertheless still suggests a clear benefit for earlier treatment in terms of preventing hospitalization in high-risk individuals 7 . Notably, antiviral therapy is not a risk factor for rebound in our model or in clinical cohorts if administered late during infection 36 .…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have defined rebound using criteria with varying virologic thresholds, timing, and sampling frequency (30) . A rebound was sometimes defined when a positive test was observed after a negative test (31) . In EPIC-HR, treatment was started within the first 5 days of symptoms (our intermediate treatment group) and rebound was defined as a 0.5 log increase on days 10 and/or 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation